Soil Strength and Water Infiltration Under Reduced and Conventional Tillage in a Typic Haplustepts of Lamongan District - Achmad Rachman (Balai Besar Penelitian dan Pengembangan Sumberdaya Lahan Pertanian, 2016)
Abstract. The ability of upland non-irrigated soil to absorb and store water is critical to to provide sufficient moisture for crop grown in dry season. The objective of this study was to evaluate the effects of tillage, reduced (RT) and conventional tillage (CT), on infiltration rate and soil penetration resistance (soil strength) in soil with ustic moisture regime planted with corn. The experiment was conducted on a site, which had been continuously planted with corn twice a year. The predominant soil was Typic Haplusteps. Six positions, 15 meters a part, were chosen within each treatment to measure infiltration rate and soil strength. The mean infiltration rate values were higher under CT (91.87 ± 18.99 mm h-1) than under RT (64.36 ± 30.97 mm h-1). The amount of water infiltrated in CT is 1.4 times higher than in RT. The RT induced the formation of near surface compacted layer with a soil strength of 850 kPa, 2 times higher than under CT at the same depth. The compacted layer is expected to be responsible for lowering infiltration rate under RT. The highest correlation (R2 = 0.83) between qs and Ksat under RT was found at the second depth (8 to 12-cm) and third depth (16 to 20-cm) for CT (R2 = 0.73) indicating that soil layer with the highest soil strength was responsible to control water infiltration. The infiltration models tested (Parlange, the Green and Ampt, and Kostiakov) fit well with the measured data (r2 = 0.99–1.00). It is recommended to conduct deep tillage (20 – 25 cm) once a year to maintain favorable soil structure for water infiltration and root growth.Abstrak: Kemampuan lahan tadah hujan untuk menyerap dan menyimpan air sangat penting dalam kaitannya dengan penyediaan kelembaban tanah yang optimum untuk pertumbuhan tanaman pada musim kemarau. Tujuan dari penelitian ini adalah untuk mengevaluasi pengaruh pengolahan tanah terbatas (RT) dan konvensional (CT) terhadap laju infiltrasi dan ketahanan penetrasi (kekuatan) tanah pada tanah dengan regim kelembaban ustic yang ditanami jagung. Penelitian dilaksanakan pada tanah Typic Haplusteps yang ditanami jagung 2 kali dalam setahun. Pengukuran infiltrasi dan kekuatan tanah dilakukan di enam titik, masing-masing berjarak 15 meter, pada tiap perlakuan. Rata-rata laju infiltrasi pada perlakuan CT adalah 91.87 ± 18.99 mm jam-1 lebih tinggi dibanding pada RT yaitu 64.36 ± 30.97 mm jam-1. Volume air yang terinfiltrasi pada perlakuan CT adalah 1,4 kali lebih banyak dibanding pada perlakuan RT. Perlakuan RT menyebabkan terbentuknya lapisan padat dibawah permukaan tanah dengan kekuatan tanah sebesar 850 kPa, 2 kali lebih besar dibanding perlakuan CT pada kedalaman yang sama. Lapisan padat pada perlakuan RT diduga sebagai penyebab rendahnya laju infiltrasi pada perlakuan tersebut. Korelasi tertinggi (R2 = 0.83) antara qs dan Ksat diperoleh pada kedalaman kedua (8-12 cm) untuk perlakuan RT dan pada kedalaman ketiga (16-20 cm) untuk perlakuan CT (R2 = 0.73) menunjukkan bahwa lapisan tanah yang paling padat mengontrol laju infiltrasi. Ketiga model penduga infiltrasi yang diuji (Parlange, Green and Ampt dan Kostiakov) berkesesuaian sangat baik dengan infiltrasi hasil pengukuran (r2 = 0.99–1.00). Berdasarkan hasil penelitian ini, direkomendasikan untuk melakukan olah tanah dalam (20 – 25 cm) sekali dalam setahun untuk menjaga agar tanah tetap gembur sehingga memperbaiki laju infiltrasi dan pertumbuhan akar.